OPTIMALISASI PERAN GELOMBANG OTAK THETA DAN ATENSI PADA PEMBELAJARAN KETERAMPILAN MEMUKUL SOFTBALL - Rizky Maulana, - (2019)
The purpose of this research is to know the correlation between theta brainwaves, attention, and hitting skills on softball learning. The method used in this study is a quantitative descriptive using multiple assessment designs. The population in this study were students of UPI Bandung Softball/Baseball extracurricular. Total population sampling will use in this research, but because of some problem, this research only use 8 sample. The calculation results of correlation between Theta Brain Waves with Attention obtained p-value of 0,000 ≤ 0.05 with an r value 0.885 with a positive interaction between theta brain waves with attention. In the second hypothesis between theta brain waves and hitting skills obtained p-value of 0.002 ≤ 0.05 with an r value 0.2, it show a positive functional correlation between theta brainwaves with Hitting Skills. Furthermore, the test between Attention and Hitting Skills obtained a p-value of 0,000 ≤ 0.05 with an r value 0.229, it describe a positive functional relationship between attention and hitting skill.